ECONOMIC THEORY IN RELATION TO ACCOUNTING VALUATIONS. - Paton, W. A. (The Accounting Review, 1931)
Abstract The article discusses economic theory in relation to accounting valuations. All items which are included under the term assets may be very roughly divided, for the purpose in hand, into two groups, more or less accurately designated as follows, repositories for funds and summations of costs. In the first may be placed cash in its various forms, account, notes, bonds and other claims for money and securities or rights readily realizable in money if not representing sums to be collected at specified times. In the second group are organization and development charges, land and wasting assets, structures and equipment of all types, long and short-term prepayments and various classes of inventories. As in most classifications there are many doubtful cases, one division shades into the other. Finished goods produced under contract, for example, are from the standpoint of both economic and legal character very closely allied to ordinary receivables. As a rule the valuation of items in the first group is a relatively simple matter, depending primarily upon legal conditions, simple arithmetical calculations and judgments as to good faith and responsibility of debtors. Further, in this group of cases there is ordinarily little to be gained by attempting to apply interpretations and reasoning of economics.